2004
DOI: 10.2169/internalmedicine.43.1042
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Associated with Wilson's Disease

Abstract: A 23-year-old man was admitted to our department due to hemorrhage from gastric varices. He had been diagnosed as having Wilson's disease at the age of 17. Abdominal ultrasonography and computed tomography (CT) showed portal thrombosis and a large mass occupying most of the right lobe in the liver. The tumor was diagnosed as hepatocellular carcinoma (HCC) by image views and tumor markers. He died 3 months after the diagnosis, and an autopsy was performed. Histologic examination of the tumor showed moderately t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 16 publications
(10 reference statements)
3
24
0
1
Order By: Relevance
“…However, Opalski cells, said to be pathognomonic of copper toxicity in the brain, were absent, in concordance with a former publication [15]. In our patient, CCC developed on a cirrhotic liver, similarly to HCC, as previously published [6,16]. …”
Section: Discussionsupporting
confidence: 92%
“…However, Opalski cells, said to be pathognomonic of copper toxicity in the brain, were absent, in concordance with a former publication [15]. In our patient, CCC developed on a cirrhotic liver, similarly to HCC, as previously published [6,16]. …”
Section: Discussionsupporting
confidence: 92%
“…In cases 10-16, the HBsAg and HCV antibodies were assayed and found to be negative in each patient (4,(17)(18)(19)(20)(21). In the present case, anti-HCV, HBsAg, and anti-HBc were all negative, and WD was thought to have an etiological relationship with the HCC.…”
Section: Discussionmentioning
confidence: 51%
“…On the other hand, Sone et al reported that use of a copper-chelating agent reduced the risk of HCC in Long-Evans cinnamon rats, an animal model of WD (22). In addition, some studies have found that copper may prevent the occurrence of HCC (17,23). In the present case, the results of a liver biopsy conducted following RFA therapy showed improvement after administration of a copper chelator.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of a hepatoma developing in this situation is low, at 1 in 400 lifelong, but recent studies would suggest hepatocellular carcinoma is more common in Wilson's disease than appreciated. [88][89][90] Some authors do not advocate routine hepatoma surveillance in cirrhosis related to Wilson's disease. 8,91 In practice however, clinicians will often opt for hepatoma surveillance, especially in the elderly.…”
Section: Initial Therapymentioning
confidence: 99%